Biosecretion of higher halophilic lipase by a novel Bacillus amyloliquefaciens AIKK2 using agro-waste as supporting substrate. (September 2018) - Musa, Haliru; Kasim, Farizul Hafiz; Gunny, Ahmad Anas Nagoor; Gopinath, Subash C.B.; Ahmad, Mohammad Azmier
Graphical abstract: Highlights: Simultaneous screening of halophilic strains & agro-substrates was conducted. Bacillus amyloliquefaciens AIKK2 has the best lipase secretion on coconut fibre. Enhanced lipase secretion obtained after optimization by One-Factor-At-A-Time. Lipase with thermal stability at 50 °C, at moderate NaCl and solvent tolerance. Abstract: Lipase secretion by halophilic strains under solid state fermentation has been relatively understudied, especially when utilizing agro-industrial substrates. Eleven halophilic bacterial strains were locally isolated and screened for lipase secretion. All the strains were subsequently subjected to the screening on various agro-industrial substrates for the lipase production, and to assess the best supporting substrate. The halophilic strain with the maximum lipase secretion (0.264 U/g) potential was selected and identified as Bacillus amyloliquefaciens AIKK2. Coconut fibre was found the best supporting substrate for halophilic lipase secretion and influence of nutritional and environmental parameters on halophilic lipase secretion was determined using One-Factor-At-A-Time. The optimized experiment was conducted at 6% glucose, 9% NaCl, 40 °C, and 200 rpm agitation speed resulted in the enhanced lipase secretion (0.29 U/g). Further, halophilic lipase characterization studies revealed that the enzyme was thermally stable at 50 °C, showed the improved activity at moderate NaCl and rare tolerance in hydrophilic solvents.